DINAMIKA PARTAI POLITIK DALAM PENGAMBILAN KEBIJAKAN BANTUAN KEMANUSIAAN INDONESIA KE ROHINGYA TAHUN 2017 - Abdul Halim; Khairunnas Khairunnas (Jurusan Ilmu Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Sriwijaya, 2021)
Indonesia is the first and only country that can open space for dialogue and access to humanity in the conditions of the humanitarian crisis in 2017. Indonesia's achievements cannot be separated from the domestic pressure that has occurred in Indonesia to pressure the government to take responsive action. The humanitarian crisis is getting worse. and the common identity of the Indonesian Muslim community and the Rohingya. One of the domestic demands was voiced by political parties in Indonesia. This study aims to see how the dynamics that occur in Indonesia in the decision-making of Indonesian humanitarian aid to the Rohingya. This study used a descriptive qualitative method with a literature database supported by policy influencers theory focused on parties’ influences. The findings of this study indicate that political parties in Indonesia are divided into two ideas in responding to the humanitarian crisis problem of the Rohingya ethnicity, some focus on providing humanitarian assistance and some focus on Indonesian firm action against the Myanmar government.